American Babylon : Race and the Struggle for Postwar Oakland - Self, Robert O., 1968- (Book collections on Project MUSE., 2003)
This volume demonstrates that the history of civil rights and black liberation politics in California did not follow a southern model, but represented a long-term struggle for economic rights that began in World War II and continued through the rise of the Black Panthers in the late 1960s